Use of Systematic Search and Review to Examine School Library Learning Environment Concepts - Schultz-Jones, Barbara; Farabough, Michelle; Ledbetter, Cynthia (Qualitative and Quantitative Methods in Libraries, 2019)
To examine the use of the term learning environment by the school library community we conducted a rigorous review of publications in 2015 and a confirmatory review in 2018. Since library and information science (LIS) in the United States has no professionally accepted tiered or ranked list of journals, a broad critical literature review was proposed using systematic search and review. The resulting dataset of 45 publications were appraised and synthesized for research evidence about how primary and secondary school libraries have defined and implemented various factors, toward describing and evaluating a learning environment. A content analysis was performed using message ideas as the unit of analysis on words used to explicitly describe the concept of learning environment. Element categories were proposed and syntaxes were reviewed until 10 mutually agreed-upon elements of school library learning environments were determined as supported by the literature. Few evaluation methods were identified. Challenges with employing the systematic search and review process to LIS concepts are discussed.